Leiomyosarcoma of inferior vena cava: A case series of four cases - Rajni Yadav; Kamal Kataria; Sandeep R Mathur; V Seenu (Indian Journal of Pathology and Microbiology, 2012)
Vascular leiomyosarcomas are rare tumors, arising most frequently from inferior vena cava (IVC). They are mostly seen in sixth decade, with a female predominance. Their diagnosis is often challenging, as patients may present with non-specific complaints such as dyspnea, malaise, weight loss, abdominal pain, or back pain, preceding the diagnosis by several years. Leiomyosarcoma of the IVC most frequently occurs in the middle segment. The final diagnosis can be made by an ultrasound or computed tomography guided biopsy. Because of limited experience with this disease, optimal management of IVC leiomyosarcoma is unknown. Curative surgical resection remains the current treatment of choice for primary leiomyosarcoma of IVC. Neoadjuvant therapy may be given to downsize the tumor and increase resectability rates. Nonetheless, when complete resection is not possible, debulking combined with radiation therapy still provides good palliation. We, hereby, report four cases of this rare entity with emphasis on management.